Taxonomic notes on the genus Protanilla (Hymenoptera: Formicidae: Leptanillinae) from Taiwan - Hsu, Po-Wei; Hsu, Feng-Chuan; Hsiao, Yun; Lin, Chung-Chi (Zootaxa, 2017)
A new species of Protanilla Taylor, 1990, P. jongi sp. nov., from Taiwan is described and illustrated, along with a supplementary description of the queen morphology of P. lini Terayama, 2009 and biological notes of Protanilla species. Furthermore, Furcotanilla Xu, 2012 is considered a junior synonym of Protanilla on reanalysis of purported diagnostic characters. A key to the world fauna of genus Protanilla based on the worker caste is provided.